Transformative learning in clinical reasoning: a meta-synthesis in undergraduate primary care medical education - Abdul Rahman, Nur Faraheen; Davies, Nathan; Suhaimi, Julia; Idris, Faridah (Taylor and Francis Group, 2023)
Clinical reasoning is a vital medical education skill, yet its nuances in undergraduate primary care settings remain debated. This systematic review explores clinical reasoning teaching and learning intricacies within primary care. We redefine clinical reasoning as dynamically assimilating and prioritising synthesised patient, significant other, or healthcare professional information for diagnoses or non-diagnoses. This focused meta-synthesis applies transformative learning theory to primary care clinical reasoning education. A comprehensive analysis of 29 selected studies encompassing various designs made insights into clinical reasoning learning dimensions visible. Primary care placements in varying duration and settings foster diverse instructional methods like bedside teaching, clinical consultations, simulated clinics, virtual case libraries, and more. This review highlights the interplay between disease-oriented and patient-centred orientations in clinical reasoning learning. Transformative learning theory provides an innovative lens, revealing stages of initiation, persistence, time and space, and competence and confidence in students’ clinical reasoning evolution. Clinical teachers guide this transformation, adopting roles as fortifiers, connoisseurs, mediators, and monitors. Patient engagement spans passive to active involvement, co-constructing clinical reasoning. The review underscores theoretical underpinnings’ significance in shaping clinical reasoning pedagogy, advocating broader diversity. Intentional student guidance amid primary care complexities is vital. Utilising transformative learning, interventions bridging cognitive boundaries enhance meaningful clinical reasoning learning experiences. This study contributes insights for refining pedagogy, encouraging diverse research, and fostering holistic clinical reasoning development.